Wozu brauchen wir eigentlich noch Geographieunterricht? Wider die subjektivistische Wende in der Geographiedidaktik - Uhlenwinkel, Anke (Journal of Geography Education, 2015)
While the international discourse in geography education is focusing on powerful knowledge as a concept to further geography teaching in schools, the German discussion seems to move away from such ideas even when it is refocusing on subject content. This article will demonstrate the German development using one case only and revealing its argumentative approach. It will set out showing how a misinterpreted version of Henri Lefèbvre’s production of space has been made the basis for curriculum planning, emphasizing the re-conceptualization of a Marxist theory from the perspective of individualistic approaches. It will then go on to show how this re-conceptualization influences the pedagogical and the societal component of geography education. In relation to the pedagogical component it will be become clear that the authors only consider it as part of a theoretical argument based on a number of different education theories. Lefèbvre’s theory is randomly correlated with each of the seven education theories brought forward, making it fit in with each and every one of them. Relating to the societal component and in stark contradiction to the original theory the new approach turns out to be rather traditional and conservative. Consequently its only achievement seems to be the importation of approaches from other disciplines without integrating them into geographical conceptual thinking. It is feared that this will neither help school geography nor the academic discipline of geography education. Rather it will jeopardize both.